Treatment of high risk myelodysplastic syndrome - Nicolaus Kröger (Haematologica)
The myelodysplastic syndrome (MDS) is considered to be a heterogeneous myeloid malignancy with a common origin in the hematopoietic stem cell compartment, generally divided into lower and higher risk. While treatment goal for lower risk MDS (LR-MDS) is to decrease transfusion burden and transformation into acute leukemia major aim for high risk MDS is to prolong survival and ultimately cure. While novel agents such as luspatercept or imetelstat have recently been approved as new treatment options for LR-MDS, hypomethylating agents (HMA) remain currently the only approved non-transplant option for HR-MDS and is the standard of care for non-transplant-eligible patients. Combinations with other drugs as first-line treatment has to date not proven more efficacious than monotherapy in HR-MDS, and outcome after HMA failure is poor. The only potential cure and standard of care for eligible patients is allogeneic stem cell transplantation (HSCT) and even if the number of transplanted – especially older – MDS patients increased over time due to a better management and donor availability the majority of MDS patients will not be eligible for this curative approach. Current challenges encompass to decrease the relapse risk, the main cause of HSCT failure. This review will summarize current knowledge of options of transplant- and non-transplant treatment approaches for these patients and demonstrate the unmet clinical need for more effective therapies.